HUBUNGAN TINGKAT PENDIDIKAN DENGAN PERILAKU PENGGUNAAN OBAT RASIONAL - Amir Kemal Sidiq (Journal of Pharmacy Tiara Bunda, 2025)
This study analyzes the correlation between education level and rational drug use behavior among communities in East Jakarta. The objective was to determine whether higher levels of education are associated with better understanding and implementation of rational drug use. A cross‑sectional design was employed using structured questionnaires and simple random sampling. The results showed a significant positive relationship between education level and rational drug use practices. Respondents with higher education demonstrated better knowledge, attitudes, and behavior in using medicines appropriately. These findings highlight the importance of health education and literacy programs to improve rational drug practices in the community